2001
DOI: 10.1097/00005537-200112000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Scissors versus Cold Dissection Tonsillectomy: A Prospective, Randomized, Multi‐Unit Study

Abstract: Bipolar scissors tonsillectomy is a safe technique with a similar morbidity to the cold dissection method. Its use is associated with a significant decrease in both surgical time and blood loss compared with the cold dissection method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 19 publications
(22 reference statements)
5
39
1
2
Order By: Relevance
“…In bipolar electrocautery the spread of heat to the tissue and its environment is less than the monopolar where as in cold dissection method there is no spread of heat to the tissue thereby tissue damage is less. [7][8][9] In the present study 22 males and 18 females underwent tonsillectomy for recurrent tonsillitis indicating a slight preponderance for male which is in concordance with Khan AR et al study.…”
Section: Discussionsupporting
confidence: 89%
“…In bipolar electrocautery the spread of heat to the tissue and its environment is less than the monopolar where as in cold dissection method there is no spread of heat to the tissue thereby tissue damage is less. [7][8][9] In the present study 22 males and 18 females underwent tonsillectomy for recurrent tonsillitis indicating a slight preponderance for male which is in concordance with Khan AR et al study.…”
Section: Discussionsupporting
confidence: 89%
“…Cautery use in tonsillectomy was first defined in 1962 [3,4]. Further, Andrea defined the first microsurgical bipolar cautery technique in 1993 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Especially postoperative pain in pediatric patients gives way to dehydratation and delays in oral intake, and these in turn have a negative effect on the patients' analgesic use and the period of normalization. Local/systemic analgesic use [6,7], different instruments and techniques (unipolar cautery, bipolar cautery, dissection) [1], and the recent subtotal removal of the tonsils, "tonsillotomy," (microdebrider, CO2 laser, low temperature plasma knife, radiofrequency) in selected cases are among the ways that are currently under consideration in order to solve the problem of postoperative pain [2,3,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Electro caurtery dissection method of tonsillectomy had higher incidence of bleeding as compared to the cold dissection in our study. In the recent studies it has been observed that the reactionary and secondary hemorrhage rates were unaffected by the surgical methods used [40][41][42][43]. The overall rate of transfer the patient to operating room under general anesthesia for control of post tonsillectomy bleeding varied from 0.93 to 2.9% in the literature [44][45] and incidence of such patients was 57.1% (20/35 bleeding patients) in one of the reports [38].…”
Section: Discussionmentioning
confidence: 99%